Ascorbic acid-2 glucoside mitigates intestinal damage during pelvic radiotherapy in a rat bladder tumor model. (4th May 2022) - Ito, Yasutoshi; Yamamoto, Tetsuo; Miyai, Kosuke; Take, Junya; Scherthan, Harry; Rommel, Anna; Eder, Stefan; Steinestel, Konrad; Rump, Alexis; Port, Matthias; Shinomiya, Nariyoshi; Kinoshita, Manabu
Abstract: Purpose: Ascorbic acid is a strong antioxidant and has potent radioprotective effects on radiation injuries. Ascorbic acid 2-glucoside (AA2G) is a stabilized derivative of ascorbic acid and rapidly hydrolyzed into ascorbic acid and glucose. Since there is the possibility that AA2G treatment interferes with the antitumor activity of radiotherapy, we investigated the effect of AA2G treatment during radiotherapy on acute radiation enteritis and antitumor activity of radiotherapy in rats. Materials and methods: AY-27 rat bladder tumor cells were used to induce bladder tumors in rats. Two weeks after inoculation rats received fractionated pelvic radiotherapy in eight fractions for 4 weeks totaling 40 Gy. During radiotherapy, one group of rats received per os AA2G (ascorbic acid: 250 mg/kg/day) and its bolus engulfment (ascorbic acid: 250 mg/kg) 8 h before each X-irradiation fraction. Seven days after the last X-irradiation, we studied histology, DNA double strand break (DSB) damage (by 53BP1 foci staining), and the M1/M2 macrophage response by immunohistochemistry of paraffin-fixed bladder and intestinal tissues. Results: AA2G treatment reduced the intestinal damage (shortening of villi) but did not reduce antitumor effectiveness of radiotherapy against bladder tumors. Like the controls, AA2G-treated rats showed no residual tumor lesions in the bladder after X-irradiation. Both AA2G-treated and control groups showed similar persistent DSB damage (53BP1 foci) both in bladders and ilea seven days after radiotherapy. Radiotherapy tended to reduce CD163 + M2 macrophages, which are considered as an anti-inflammatory subtype favoring tissue repair, in the bladders. X-irradiation also reduced the occurrence of M2 macrophages in the ilea. AA2G treatment significantly increased CD163 + /CD68 + macrophage ratio in the ilea of rats after pelvic irradiation in comparison to the sham irradiated control rats. AA2G treatment increased, albeit not significantly, the CD163 + /CD68 + macrophage ratio in the irradiated bladders relative to the control irradiated rats. On the other hand, bladders and ilea of the irradiated rats with and without AA2G treatment showed similar frequencies of CD68 + macrophages. Conclusions: AA2G treatment mitigated radiation-induced intestinal damage without reducing antitumor activity after fractionated pelvic radiotherapy against bladder tumors in rats. The beneficial effect of AA2G treatment seems to promote a restoration of the M2 answer as well as tissue remodeling and wound healing. Similar residual DNA damage in bladders and ilea seven days post-irradiation is consistent with tumor control in both groups.